Regionalization of the INIBAP information system: Report of an international meeting, 14-16 Oct. 1991, Montpellier, France - Picq, C.; International Network for the Improvement of Banana and Plantain (1992)
A review of the information requirements and priorities to be handled for the INIBAP information network. Regions concerned: Latin America and the Caribbean, Asia and the South Pacific, West, Central and East Africa. Description of the research priorities, facilities, products and services used in the information network.